FATIGUE ANALYSIS OF CATENARY MOORING SYSTEM DUE TO HARSH ENVIRONMENT IN FOLLOWING SEAS - Fuad Mahfud Assidiq (Jurnal PPI Dunia, 2018)
In the operation, Floating Production Unit (FPU) will get dynamic loads on the structure periodicallysuch as the mooring line responses. The aim of the present study to discuss fatigue life on catenarymooring system refers to the comparison of using or without using the Single Line Freestanding Riser(SLFR), the operational design and installation conditions at FPU Gendalo-Gehem and located in theMakassar Strait using the six-strand wire rope with 0,115 meters outer diameter and 1.200 meters lengthwill be fatigue life analysed. The FPU motion observation shows the highest Response AmplitudeOperator (RAO) surge, sway, heave, roll, pitch, and yaw motion due to harsh environments are 0,615m/m, 1,01x10-6 m/m, 1,048 m/m, 1,14x10-5 0/m, 2,23 0/m, and 9,08x10-8 0/m. It means that theamplitude response will always be smaller than the wave amplitude coming up. Taking into RAOmotion calculation, the fatigue life on catenary mooring systems for following seas are 445 years inmooring line 1 and mooring line 8 with using SLFR while without using SLFR for 5.461 years inmooring line 1. The structure is still in safe condition because of the design safety factor about 300years.